Self‐criticism and self‐reassurance as mediators between mental health attitudes and symptoms: Attitudes toward mental health problems in Japanese workers. Issue 2 (13th December 2018) - Kotera, Yasuhiro; Gilbert, Paul; Asano, Kenichi; Ishimura, Ikuo; Sheffield, David
Abstract : Japanese workers suffer high rates of mental health symptoms, recognised recently by the Japanese government, which has enacted workplace well‐being initiatives. One reason for poor mental health concerns negative attitudes about mental health problems such as shame, which may be mediated by self‐reassurance and self‐criticism. This study aimed to evaluate shame‐based attitudes toward mental health problems and explore the relationship between mental health attitudes, self‐criticism, self‐reassurance, and mental health symptoms. Japanese workers ( n = 131) completed three measures: attitudes toward mental health problems, mental health symptoms, and self‐criticism/reassurance. A high proportion of workers reported negative attitudes about mental health problems. There were strong relationships between mental health attitudes, mental health symptoms, self‐criticism, and self‐reassurance. Path analyses revealed that the total and indirect effects (through self‐criticism and self‐reassurance) of mental health attitudes on mental health were larger than the direct effect alone. Hated‐self and family reflected shame were identified as predictors for mental health symptoms. The findings suggest the importance of self‐criticism and self‐reassurance in mental health and mental health attitudes. Implications for help‐seeking behaviours also are discussed. Interventions aimed at reducing self‐criticism and enhancing self‐reassurance are recommended to improve mental health attitudes and increase help‐seeking in Japanese workers.